SENTIMEN PENGGUNA X TERHADAP KEYWORD "PRABOWO GEMOY" SEBAGAI PERSONAL BRANDING PRABOWO PADA PEMILIHAN PRESIDEN 2024 - Bajuri, Diding; Fahrudin, Atef; Nurmeilani, Cindy Alya (JIKE : Jurnal Ilmu Komunikasi Efek, 2024)
This research aims to analyze the sentiment of X platform users towards the use of the keyword "Prabowo Gemoy" as a personal branding strategy for Prabowo Subianto in the context of the 2024 Presidential Election. By employing a mixed-method approach that combines qualitative and quantitative methods, this study explores public perceptions of Prabowo's efforts to build an image that is closer to young voters through the "Prabowo Gemoy" branding. Data were collected from the X platform using the keyword "Prabowo Gemoy" during the period of 01/12/2023 to 13/02/2024, resulting in 517 data points that were analyzed quantitatively to measure sentiment statistics and communication networks, as well as qualitatively through text analysis to understand the context behind the sentiments. The results of the sentiment analysis show a dominance of positive sentiment (65.38%), followed by neutral sentiment (22.05%), and negative sentiment (12.57%), indicating that the "Prabowo Gemoy" branding strategy has been well-received by most X platform users. Furthermore, the influencer analysis revealed key users who have significant influence in disseminating related content, while the word cloud visualization identified dominant keywords in the discussions. These findings provide valuable insights for Prabowo Subianto's campaign team to refine their branding strategy and content dissemination on social media in an effort to reach young voters.